Phytochemical Screening and Antioxidant Activity of Tampoi Leaves (Baccaurea macrocarpa (Miq.)Mull.Arg ) by Leaf Age and Solvent Type - Sujarwati; Mayta Novaliza Isda; Desna Tasya Rahmadhani; Ulfatur Rohmah (JURNAL SAINS NATURAL, 2023)
Tampoi (Baccaurea macrocarpa (Miq.) Mull.Arg) is a member of the genus Baccaurea which is distributed mainly in the regions of Borneo and Sumatra. The use of tampoi can be done by exploring the potential of tampoi plants as medicinal plants. The research was conducted to determine the content of secondary metabolites and the results of the analysis of the antioxidant activity of tampoi leaves. The leaf extraction process uses polar solvents in the form of water, 70% ethanol, 70% methanol and non-polar in the form of chloroform, toluene, and n-hexane. Analysis of antioxidant activity using the DPPH method (2,2-diphenyl-1-picrylhydrazil). The results showed that polar solvents are better used in extracting secondary metabolites of tampoi leaves in non-plar solvents. The conclusion of this study is the types of secondary metabolites contained in tampoi leaves, namely alkaloids, flavonoids, saponins, tannins, steroids, and triterpenoids. Young tampoi leaves have a stronger antioxidant activity value than old leaves. The most effective solvent for extracting secondary metabolite compounds of tampoi leaves is 70% methanol.